Indywidualizm amerykańskiej Starej Prawicy - Jacek Spendel (Historia i Polityka, 2011)
The article is dedicated to the philosophy and history of the Old Right movement in United States of America. At the beginning, author discusses the historical roots, ideological structure, and principles of the Old Right with important figures behind it. The next part of the article is devoted to the presence of the movement in the American political arena: it’s alliances, enemies, and political representation. A substantial part of the article is based on the Old Right’s arguments against President Roosevelt’s New Deal in all it’s aspects. The consequent anti-interventionist position of the Old Right pushed them to opposition to the US military presence in World War I and World War II. That unique but ideologically coherent standpoint is discussed in the later part of the article. It shows the popular perception of the anti-interventionist arguments, revealing not widely known facts about it. The question of the American military interventions reflected by the classical liberal principles, dominates the last part of the article. Author discusses the theory of the cold war and emerge of the New Right as a cause of the Old Right’s defeat. Finally, he summarizes the Old Right’s political positions, and predicts possible developments of that ideas in future.